Legal Certainty of the Use of Cryptocurrency as An Investment Instrument in Companies in Indonesia - Christofel Adam Sitorus; Muthia Sakti (Dinasti Research, 2025)
This study examines the legal certainty of using cryptocurrency as an investment instrument in companies in Indonesia. Although cryptocurrency is not recognized as a legal means of payment, it has been acknowledged as a tradable commodity in futures exchanges. This research utilizes a normative legal approach to analyze existing regulations, challenges encountered, and legal protections available for investors. The findings indicate that despite significant profit potential, investors still face high risks due to price volatility, insufficient legal protections, and cybersecurity threats. It is crucial for the government to formulate more comprehensive and supportive regulations to protect investors and prevent misuse and illegal practices. Additionally, an extensive educational program is needed to enhance public understanding of the risks and benefits of investing in cryptocurrency. With adequate regulation and improved public awareness, cryptocurrency is expected to contribute positively to Indonesia’s digital economic growth. This study aims to contribute to the development of policies and regulations related to cryptocurrency in Indonesia and to encourage greater public participation in this investment ecosystem.